AB0236 What Level of Disease Activity at 6 Months Predicts Achieving or Sustaining Remission at 12 Months?. (10th June 2014) - Keystone, E.; Baer, P.; Haraoui, B.; Avina-Zubieta, J.A.; Chow, A.; Sholter, D.; Choquette, D.; Rampakakis, E.; Sampalis, J.S.; Nantel, F.; Lehman, A.J.; Shawi, M.; et al.
Abstract : Background: Achievement of clinical remission in rheumatoid arthritis (RA) is a process that may take several months. Identification of clinical signs predicting future remission may assist physicians in clinical decision making. Objectives: The aim of this analysis was to describe the association between DAS28-ESR scores at 6 months and remission at 12 months in RA patients treated with infliximab (IFX) in a real-world, clinical practice setting. Methods: BioTRAC is an ongoing, prospective Canadian registry of patients initiating treatment for RA, ankylosing spondylitis (AS), or psoriatic arthritis (PsA) with IFX or golimumab as first biologics or after having been treated with a biologic for <6 months. Eligible patients for this analysis included RA patients treated with IFX who were enrolled between 2002 and 2012 and had available DAS28 data at 6 and 12 months of follow-up. The association between DAS28-ESR score at 6 months and remission achievement at 12 months was assessed with logistic regression. Receiver operator curve (ROC) analysis was used to determine the optimal cut-off points for achieving and maintaining remission. Results: A total of 293 patients were included with a mean (SD) age of 56 (13.5) years and disease duration of 10.0 (9.7) years. Mean (SD) DAS28 was 3.8 (1.5) and 3.5 (1.5) at 6 and 12 months, respectively, and the percent with DAS28-ESR remission was 24.6% and 27.0%. Of the patients in remission at 6 months, 65.3% sustained the remission at 12 months, while of those not in remission at 6 months, 14.5% achieved remission at 12 months (P<0.001). Logistic regression analysis showed a significant inverse association between DAS28-ESR score at 6 months and the likelihood of achieving remission at 12 months [for each increase in DAS28-ESR score by one unit there was a 64.6% lower probability of achieving remission; P<0.001]. ROC curve analysis identified a DAS28 score at 6 months ≤3.54 as most accurately predicting remission at 12 months with a sensitivity of 82% and a specificity of 70% (Fig. 1A ). Stratified analysis showed that, among patients in remission at 6 months, a DAS28 score of ≤2.13 was the optimal cut-off for predicting sustained remission at 12 months (68% sensitivity, 64% specificity) (Fig. 1B ). Conclusions: The results of this analysis demonstrate that a DAS28-ESR target of ≤3.54 at 6 months maximizes the likelihood of remission at 12 months while a value of ≤2.13 should be targeted for optimal sustainment of remission. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4755